Analisis Kebergunaan, Kemudahan, dan Kepercayaan pada Intention to Use Mobile Banking Bank BUMN - Gunawan, Angela Melia; Tileng, Kartika Gianina (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
State-owned banks play an important role in strengthening the mobile banking trend by providing services that are innovative and attractive to the public. State-owned banks also contribute to the State Revenue and Expenditure Budget, which influences national economic development and growth. Based on the important role of state-owned banks in strengthening the mobile banking trend and its impact on the economy, this research aims to analyze how usefulness, ease of use and trust factors influence intention to use in utilizing mobile banking services at state-owned banks. This research uses a quantitative approach with surveys as a data collection method. The data obtained was analyzed using multiple linear regression analysis to identify relationships between variables. The results show that usefulness is the main factor in encouraging the use of mobile banking in state-owned banks compared to ease of use and trust. This approach is expected to help state-owned banks develop services that are more responsive to customer needs and preferences, so that they can accelerate the adoption of mobile banking services and optimize their benefits for the national economy.